Entamoeba moshkovskii Is Associated With Diarrhea in Infants and Causes Diarrhea and Colitis in Mice - Shimokawa, Chikako (Oxford University Press, 2012)
Background.Entamoeba moshkovskii is prevalent in developing countries and morphologically indistinguishable from pathogenic Entamoeba histolytica and nonpathogenic Entamoeba dispar. It is not known if E. moshkovskii is pathogenic. Methods.Mice were intracecally challenged with the trophozoites of each Entamoeba spp. to test the ability to cause diarrhea, and infants in Bangladesh were prospectively observed to see if newly acquired E. moshkovskii infection was associated with diarrhea. Results.E. moshkovskii and E. histolytica caused diarrhea and weight loss in susceptible mice. E. dispar infected none of the mouse strains tested. In Mirpur, Dhaka, Bangladesh, E. moshkovskii, E. histolytica, and E. dispar were identified in 42 (2.95%), 66 (4.63%), and 5 (0.35%), respectively, of 1426 diarrheal episodes in 385 children followed prospectively from birth to one year of age. Diarrhea occurred temporally with acquisition of a new E. moshkovskii infection: in the 2 months preceding E. moshkvskii-associated diarrhea, 86% (36 of 42) of monthly surveillance stool samples were negative for E. moshkovskii. Conclusions.E. moshkovskii was found to be pathogenic in mice. In children, the acquisition of E. moshkovskii infection was associated with diarrhea. These data are consistent with E. moshkovskii causing disease, indicating that it is important to reexamine its pathogenicity.